Carcinoma gástrico - Víctor H. Covelli Otero; Fernando Abaúnza O. (Revista de la Facultad de Medicina, 1963)
755 cases of gastric carcinoma were studied that had been treated at the Hospital San Juan de Dios, of Bogotá, from 1953 to 1960. At the time of consultation the disease was in an advance stage; it appears that incidence is high if a comparison is made with other published studies, and the disease is on the increase; its higher occurrence in men is confirmed, predominating in men between the ages of 40 to 60 years. Attention is called to the four principal symptoms: pain, anorexia, vomiting and loss of weight; and the high operative mortality' is emphasized. 1. It is necessary to insist on campaings that will make feasible the earlier diagnosis of gastric carcinoma. 2. Patients should be more carefully evaluated surgically. 3. Intestinal parasitism should not be a definitive diagnosis in our midst, when a patient complains of epigastric pain, or anorexia, or vomiting, or loss of weight. 4. No relationship was found between the blood group distribution and gastric carcinoma. 5. The social welfare service should establish a better follow up (control) over the patients operated on.